Alive! : airplane crash in the Andes mountains - Werther, Scott P. (New York : Children's Press, 2003)
Tells the story of the 1972 plane crash that stranded several members of a Uruguayan rugby team in the Andes Mountains for two months, struggling to survive.
Includes bibliographical references (p. 44) and index.
5.7
Young Adult
Keywords: Survival after airplane accidents, shipwrecks, etc. -- Juvenile literature; Aircraft accidents -- Andes Region -- Juvenile literature; Cannibalism -- Andes Region -- Juvenile literature; Survival; Aircraft accidents -- Andes Region; Cannibalism -- Andes Region; Survival after airplane accidents, shipwrecks, etc; Aircraft accidents -- Andes Region; Cannibalism